Complementary influence of green-roof and roof-slab thermal conductivity on winter indoor warming assessed by finite element analysis - Taibing Wei; C.Y. Jim; Yuxin Chen; Anqi Chen; Xiaojuan Li (Energy Reports, 2022)
A green roof can modify the roof outer surface temperature (Tr) to influence indoor air temperature (Ti). Green roof design and roof-slab thermal insulation jointly determine the coupled-roof system’s thermal performance. This study investigated their joint effects on subtropical winter warming, which were seldom investigated. Custom-built houses without (bare roof) and with a 20-cm soil layer at circa 20% moisture content (soil roof) provided experiment plots to collect field data. The measured data tested the corrected finite element analysis model and simulated the combined influence of soil cover (properties kept constant) and a gradation of roof-slab thermal insulation on Tiin the unsteady heat transfer mode. Such multiple-factor and complex spatiotemporal studies are difficult using only field experiments and measurements. Average Tiwas raised by 0.44 °C on a typical winter day, bringing 4.55% energy saving to indoor-heating budget. With poor roof-slab insulation, the soil roof significantly retained indoor warmth. With improved roof-slab insulation, the soil roof’s influence on Tiwaned. A tipping point at 0.95 W/(m K) thermal conductivity signified a maximum threshold above which the green roof would not retain additional indoor heat. An upper threshold of thermal insulation at 0.35–0.05 W/(m K) was found, above which further insulation increase would not keep additional indoor warmth. Subtropical winter indoor warming by green roof was verified via two heat preservation mechanisms: retaining indoor heat to bring passive warming and delivering heat indoors to bring active warming. They were triggered by slightly warmed and notably warmed green-roof soil, respectively. The results ascertained quantitatively the complementary thermal role of green roof and roof slab. The findings can optimize the subtropical green-roof design and achieve winter indoor warming and thermal comfort.